Relationship between red cell distribution and acute heart failure in patients of one of the tertiary care centres, Gujarat - Budhdev, Shridhar J.; Dodiya, Manoj R. (International Journal of Research in Medical Sciences, 2022)
Background: Red cell distribution (RDW) is a marker of anisocytosis, inflammation and ageing. It used to differentiate anemias and is associated with chronic conditions such as chronic obstructive pulmonary disease (COPD), chronic kidney disease (CKD), malignancy, irritable bowel syndrome (IBS) etc. Aim and objectives were to study/compare RDW in patients of heart failure (HF) and healthy individuals, to observe values of RDW in patients of acute HF and controls (as per exclusion criteria), to study relationship between RDW and HFREF/HFPEF and to study correlation of RDW and age of subjects. Methods: This is an observational cross-sectional comparative hospital-based study with 105 sample size conducted in tertiary care center for the duration of 1 year. Results: Of the total 105 patients, 35 were control (healthy individuals) and 70 patients of HF (from which 48 had HFREF and 22 had HFPEF). The gender distribution was 40.4% females and 59.6% males. There is positive correlation between RDW and age of the case (Pearson correlation 0.0138 and p=0.0002). In the HFREF subgroup 35 participants and in HFPEF 16 participants were >13.6 RDW distribution. There was no significant difference in RDW distribution among two subgroups of HF cases. Conclusions: RDW is a novel and cheap marker that can be used to diagnose Heart. Longitudinal serial assessment of RDW in cases of HF might provide the severity of the disease and can help predict adverse outcomes. In rural areas, with unavailability of 2D echocardiography/expensive investigations (NTProbnp), HF can reliably be diagnosed based on raised values of RDW coupled with clinical presentation.